Layered Inequalities: land grabbing, collective land rights and afro-descendant resistance in Colombia (politics, community and society in a ... gesellschaft in einer globalisierten Welt) (2014)
In Colombia, since the 1990s, thousands of Afro-descendants have benefited from collective land rights. However, many peasants have been violently displaced in order to introduce industrial crops, while several other groups of peasants resisted these agribusiness land grabs. This book examines the layered inequalities in this process and analyzes the various paradoxes of recent Colombian development policies: the agribusiness expansions through land grabs; the land and labor conflicts that have overlapped in regions with agribusiness; and both the Afro-descendants and mestizos demand for land rights. (Series: Politics, Society and Community in a Globalized World / Politik, Gemeinschaft und Gesellschaft in einer globalisierten Welt - Vol. 16) [Subject: Latin America Studies, Human Rights, Agricultural Studies, Business]